Implementing a Large On-Campus ALN: Faculty Perspective - Kashy, Edwin; Thoennessen, Michael; Albertelli, Guy; Tsai, Yihjia (Online Learning, 2000)
This case study describes the implementation and continued operation of a large on-campus ALN for a 500-student course in introductory physics. The ALN was used to modify and complement the original course and thus represents an evolution rather than a revolution. A highly positive impact on student success rates was achieved and continues. Factors that increased faculty satisfaction and instances of dissatisfaction are presented. The potential increase in the latter with technology is of some concern.